2013
DOI: 10.3109/0284186x.2013.766362
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous radiofrequency ablation (RFA) or robotic radiosurgery (RRS) for salvage treatment of colorectal liver metastases

Abstract: (2013) Percutaneous radiofrequency ablation (RFA) or robotic radiosurgery (RRS) for salvage treatment of colorectal liver metastases, Acta Oncologica, 52:5, 971-977,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…In an attempt to compare RFA with SBRT, Stintzing and colleagues evaluated the outcomes of these two treatments in a single institution retrospective study. 27 The cohort included 60 heavily treated colorectal cancer patients. Median SBRT dose was 24-26 Gy at the 80% isodose.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to compare RFA with SBRT, Stintzing and colleagues evaluated the outcomes of these two treatments in a single institution retrospective study. 27 The cohort included 60 heavily treated colorectal cancer patients. Median SBRT dose was 24-26 Gy at the 80% isodose.…”
Section: Discussionmentioning
confidence: 99%
“…40 In comparison to other ablative techniques such as RFA, MWA produces consistently higher intertumoural temperatures, larger tumour ablation volumes, faster ablation times and less procedural pain. 39 Moreover, the heat sink effect of MWA is minimal and usually does not create ablation zone distortions in the vicinity of large blood vessels (Figure 1). 39 Most studies reported MWA to be a relatively safe method with low complication rates.…”
Section: Microwave Ablationmentioning
confidence: 99%
“…39 Moreover, the heat sink effect of MWA is minimal and usually does not create ablation zone distortions in the vicinity of large blood vessels (Figure 1). 39 Most studies reported MWA to be a relatively safe method with low complication rates. The most common complications of MWA are pain, fever, ascites, bile duct injury and pleural effusion (Table 4).…”
Section: Microwave Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with growing experience, it proves to be a valuable contribution to the treatment armamentarium of CRLM. One study compared stereotactic radiotherapy to RFA in a matched patient population and found a significantly longer local disease free survival than in the patients treated with RFA [40,41]. These findings should be confirmed by larger prospective trials.…”
Section: Discussionmentioning
confidence: 99%